2021
DOI: 10.1037/spq0000469
|View full text |Cite
|
Sign up to set email alerts
|

Teachers navigating distance learning during COVID-19 without feeling emotionally exhausted: The protective role of self-efficacy.

Abstract: In the context of the Coronavirus disease (COVID-19) outbreak, teachers faced unprecedented challenges and threats while implementing distance learning. Consequently, teachers may have experienced emotional exhaustion. The aim of our study was threefold: To explore teachers' threat appraisals, to investigate the relation between teachers' threat appraisals and their emotional exhaustion, and to examine processes protecting teachers from emotional exhaustion. Self-efficacy belief, especially, may have driven te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 64 publications
1
32
0
5
Order By: Relevance
“…The chronic stress (Stauffer & Mason, 2013 ) and high turnover (Carver‐Thomas & Darling‐Hammond, 2017 ) already rampant among school teachers in the United States (US), and in the world as a whole (Thompson, 2021 ), have risen to an unparalleled crisis during the COVID‐19 pandemic in the United States and around the world (UN News, 2020 ). Teachers, recognized as frontline workers (Pressley et al, 2021 ; Sokal et al, 2020 ), have faced additional stress (Chang & Yano, 2020) due to safety concerns (Wakui et al, 2021 ), rapid transitions to remote or hybrid teaching (Soncini et al, 2021 ), and exacerbated work‐life challenges (Kraft et al, 2021 ; Sokal et al, 2020 ). Teacher attrition is linked to student development, education quality, and academic achievement (Sorensen & Ladd, 2020 ), and as a result, pandemic‐driven teacher attrition has become an acute, global concern (Thompson, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The chronic stress (Stauffer & Mason, 2013 ) and high turnover (Carver‐Thomas & Darling‐Hammond, 2017 ) already rampant among school teachers in the United States (US), and in the world as a whole (Thompson, 2021 ), have risen to an unparalleled crisis during the COVID‐19 pandemic in the United States and around the world (UN News, 2020 ). Teachers, recognized as frontline workers (Pressley et al, 2021 ; Sokal et al, 2020 ), have faced additional stress (Chang & Yano, 2020) due to safety concerns (Wakui et al, 2021 ), rapid transitions to remote or hybrid teaching (Soncini et al, 2021 ), and exacerbated work‐life challenges (Kraft et al, 2021 ; Sokal et al, 2020 ). Teacher attrition is linked to student development, education quality, and academic achievement (Sorensen & Ladd, 2020 ), and as a result, pandemic‐driven teacher attrition has become an acute, global concern (Thompson, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it is essential to develop an instrument to measure emotional exhaustion in teachers since it has been associated with their self-efficacy (as an enduring self-regulatory trait) [ 63 ], mood [ 16 ], stress [ 64 ], anxiety [ 65 ], and depression [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Self‐efficacy has been found to be positively related to job satisfaction (Avanzi et al, 2013 ; Federici & Skaalvik, 2012 ), and negatively associated with burnout (Avanzi et al, 2013 ) and emotional exhaustion (Federici & Skaalvik, 2012 ). More recently, Soncini et al ( 2021 ) investigated teachers' experiences with remote learning during COVID‐19 and concluded that self‐efficacy was a buffer against teacher burnout. Taken together, these findings suggest that self‐efficacy may play a role in contributing to compassion satisfaction and perhaps, mitigating burnout.…”
Section: Literature Reviewmentioning
confidence: 99%